NURSING CARE OF A PATHIENT DIAGNOSED COLD CYSTIC PHYBROSIS ACCORD TO MARJORY GORDON'S MODEL: A CASE REPORT - GÜNDÜZ AKTAŞ, Nurşah; BARAN DURMAZ, Gülbeyaz (Göbeklitepe Medical Science Journal, 2024)
Cystic fibrosis is a disease that affects many systems as a result of dysfunction of exocrine glands seen in childhood. This disease, which especially affects the respiratory and digestive systems, creates a progressive picture that causes serious problems in quality of life. Therefore, the patient should be handled with a holistic approach. Nurses, who are health professionals, play an important role in the diagnosis and treatment process of the disease. In this case, the patient diagnosed with cystic fibrosis was planned to be nurtured according to Gordon's Health Patterns model. Within the scope of this model, the nursing care of the patient was examined according to 11 functional health patterns. Sick; It has been evaluated in many aspects such as perception, nutrition, excretion, sleep, sexuality and belief. In this case, the purpose of nursing care of a pediatric patient diagnosed with cystic fibrosis; The main purpose of nursing care to be applied to the patient is to relieve the patient's respiratory functions, to provide adequate nutrition, to protect against possible infections, to support growth and development, and to assist the patient and his family in the management of the disease in the process.